Dual-Homomorphic Message Authentication Code Scheme for Network Coding-Enabled Wireless Sensor Networks. (2nd July 2015) - Esfahani, Alireza; Yang, Du; Mantas, Georgios; Nascimento, Alberto; Rodriguez, Jonathan
Network coding has shown a considerable improvement in terms of capacity and robustness compared to traditional store-and-forward transmission paradigm. However, since the intermediate nodes in network coding-enabled networks have the ability to change the packets en route, network coding-enabled networks are vulnerable to pollution attacks where a small number of polluted messages can corrupt bunches of legitimate messages. Recently, research effort has been put on schemes for protecting the transmitted messages against data pollution attacks. However, most of them cannot resist tag pollution attacks. This paper presents a new homomorphic MAC-based scheme, called Dual-Homomorphic MAC (Dual-HMAC), for network coding-enabled wireless sensor networks. The proposed scheme makes use of two types of tags (i.e., MACs and D-MACs) to provide resistance against data pollution attacks and partially tag pollution attacks. Furthermore, our proposed scheme presents low communication overhead and low computational complexity compared to other existing schemes.